Examples with solutions for The Quadratic Formula: Equations with variables on both sides

Exercise #1

What is the value of x?

x4x3=2x2 x^4-x^3=2x^2

Video Solution

Step-by-Step Solution

To solve the problem x4x3=2x2 x^4 - x^3 = 2x^2 , let's proceed as follows:

  • Step 1: Set the equation to zero.
    x4x32x2=0 x^4 - x^3 - 2x^2 = 0
  • Step 2: Factor out the greatest common factor.
    The common factor among all terms is x2 x^2 .
    Factoring out x2 x^2 gives:
    x2(x2x2)=0 x^2(x^2 - x - 2) = 0
  • Step 3: Solve the factors.
    This equation breaks into two factors that can be solved separately:
    • x2=0 x^2 = 0
    • x2x2=0 x^2 - x - 2 = 0
  • Step 4: Solve x2=0 x^2 = 0 .
    Since x2=0 x^2 = 0 , we get:
    x=0 x = 0
  • Step 5: Solve x2x2=0 x^2 - x - 2 = 0 .
    This can be factored further. We look for two numbers that multiply to 2-2 and add up to 1-1.
    These numbers are 2-2 and 11, so we factor as:
    (x2)(x+1)=0 (x - 2)(x + 1) = 0
  • Step 6: Solve the quadratic factors.
    Set each factor equal to zero:
    • x2=0x=2 x - 2 = 0 \Rightarrow x = 2
    • x+1=0x=1 x + 1 = 0 \Rightarrow x = -1

The solutions to the equation x4x3=2x2 x^4 - x^3 = 2x^2 are x=1,0,2 x = -1, 0, 2 .

Therefore, the correct answer is:

x=1,2,0 x = -1, 2, 0

Answer

x=1,2,0 x=-1,2,0

Exercise #2

x3=x2+2x x^3=x^2+2x

Video Solution

Step-by-Step Solution

To solve the problem x3=x2+2x x^3 = x^2 + 2x , follow these steps:

  • Step 1: Re-arrange the equation to have all terms on one side:
    x3x22x=0 x^3 - x^2 - 2x = 0 .
  • Step 2: Factor out the greatest common factor (GCF), which is x x :
    x(x2x2)=0 x(x^2 - x - 2) = 0 .
  • Step 3: Factor the quadratic expression x2x2 x^2 - x - 2 :
    The factors of 2-2 that add up to 1-1 are 2-2 and 11. Thus, x2x2=(x2)(x+1) x^2 - x - 2 = (x-2)(x+1) .
  • Step 4: Combine the factored terms:
    x(x2)(x+1)=0 x(x-2)(x+1) = 0 .

Each factor can be set to zero to find the solutions:

  • x=0 x = 0 .
  • x2=0 x - 2 = 0 , so x=2 x = 2 .
  • x+1=0 x + 1 = 0 , so x=1 x = -1 .

The solutions to the equation are x=0,1,2 x = 0, -1, 2 .

Therefore, the correct choice from the given options is:
x=0,1,2 x = 0, -1, 2 .

Answer

x=0,1,2 x=0,-1,2

Exercise #3

Solve the following equation:

x2+3x3=x x^2+3x-3=x

Video Solution

Answer

x1=1 x_1=1 , x2=3 x_2=-3

Exercise #4

Solve the following equation:

3x217x+28=x+4 3x^2-17x+28=x+4

Video Solution

Answer

x1=4 x_1=4 , x2=2 x_2=2

Exercise #5

Solve the following equation:

4x2+9x5=74x 4x^2+9x-5=7-4x

Video Solution

Answer

x1=34 x_1=\frac{3}{4} x2=4 x_2=-4

Exercise #6

Find X

(3x+1)2+8=12 (3x+1)^2+8=12

Video Solution

Answer

x1=13,x2=1 x_1=\frac{1}{3},x_2=-1

Exercise #7

Given the equation. Find its solution

13x2+4x=8(x+3)2 13x^2+4x=8(x+3)^2

Video Solution

Answer

x1=10.21,x2=1.41 x_1=10.21,x_2=-1.41

Exercise #8

Given the following equation, find its solution

7x2+3x+8=9x+3 7x^2+3x+8=9x+3

Video Solution

Answer

No solution

Exercise #9

Solve the following equation:

10x265x+135=4x2+13x45 10x^2-65x+135=4x^2+13x-45

Video Solution

Answer

x1=10 x_1=10 x2=3 x_2=3

Exercise #10

Solve the following equation:

2x2+6x12=4x2+19x5 -2x^2+6x-12=-4x^2+19x-5

Video Solution

Answer

x1=7 x_1=7 , x2=12 x_2=-\frac{1}{2}

Exercise #11

Solve the following equation:

x2+x2=2x22x4 -x^2+x-2=-2x^2-2x-4

Video Solution

Answer

x1=2,x2=1 x_1=-2,x_2=-1

Exercise #12

Solve the following equation:

x2+3x4=2x2 x^2+3x-4=2x^2

Video Solution

Answer

No solution

Exercise #13

Find X

7x+1+(2x+3)2=(4x+2)2 7x+1+(2x+3)^2=(4x+2)^2

Video Solution

Answer

1±338 \frac{1\pm\sqrt{33}}{8}

Exercise #14

Solve the following equation:

x3+1(x1)2=x+4 \frac{x^3+1}{(x-1)^2}=x+4

Video Solution

Answer

x=3,12 x=3,\frac{1}{2}

Exercise #15

Solve the following equation:

(x+3)2=4x -(x+3)^2=4x

Video Solution

Answer

x1=1,x2=9 x_1=-1,x_2=-9

Exercise #16

Solve the following equation:

(x+2)2=(2x+3)2 (x+2)^2=(2x+3)^2

Video Solution

Answer

x1=1,x2=53 x_1=-1,x_2=-\frac{5}{3}

Exercise #17

Solve the following equation:

(x4)2+3x2=16x+12 (x-4)^2+3x^2=-16x+12

Video Solution

Answer

x=1 x=-1

Exercise #18

Solve the following equation:

(x5)25=12+2x (x-5)^2-5=-12+2x

Video Solution

Answer

x1=8,x2=4 x_1=8,x_2=4

Exercise #19

Solve the following equation:

(x+3)2=2x+5 (x+3)^2=2x+5

Video Solution

Answer

x=2 x=-2

Exercise #20

Solve the equation

2x22x=(x+1)2 2x^2-2x=(x+1)^2

Video Solution

Answer

Answers a + b